Chromothripsis and ring chromosome 22: a paradigm of genomic complexity in the Phelan-McDermid syndrome (22q13 deletion syndrome). Issue 4 (29th January 2018) - Kurtas, Nehir; Arrigoni, Filippo; Errichiello, Edoardo; Zucca, Claudio; Maghini, Cristina; D'Angelo, Maria Grazia; Beri, Silvana; Giorda, Roberto; Bertuzzo, Sara; Delledonne, Massimo; Xumerle, Luciano; Rossato, Marzia; et al.
Abstract : Introduction: Phelan-McDermid syndrome (PMS) is caused by SHANK3 haploinsufficiency. Its wide phenotypic variation is attributed partly to the type and size of 22q13 genomic lesion (deletion, unbalanced translocation, ring chromosome), partly to additional undefined factors. We investigated a child with severe global neurodevelopmental delay (NDD) compatible with her distal 22q13 deletion, complicated by bilateral perisylvian polymicrogyria (BPP) and urticarial rashes, unreported in PMS. Methods: Following the cytogenetic and array-comparative genomic hybridization (CGH) detection of a r(22) with SHANK3 deletion and two upstream duplications, whole-genome sequencing (WGS) in blood and whole-exome sequencing (WES) in blood and saliva were performed to highlight potential chromothripsis/chromoanagenesis events and any possible BPP-associated variants, even in low-level mosaicism. Results: WGS confirmed the deletion and highlighted inversion and displaced order of eight fragments, three of them duplicated. The microhomology-mediated insertion of partial Alu- elements at one breakpoint junction disrupted the topological associating domain joining NFAM1 to the transcriptional coregulator TCF20 . WES failed to detect BPP-associated variants. Conclusions: Although we were unable to highlight the molecular basis of BPP, our data suggest that SHANK3 haploinsufficiency and TCF20 misregulation, both associated with intellectual disability, contributed to the patient's NDD, while NFAM1 interruption likely caused her skin rashes, as previously reported. We provide the first example of chromoanasynthesis in a constitutional ring chromosome and reinforce the growing evidence that chromosomal rearrangements may be more complex than estimated by conventional diagnostic approaches and affect the phenotype by global alteration of the topological chromatin organisation rather than simply by deletion or duplication of dosage-sensitive genes.